Case report: Clinical features of COVID-19 vaccine-induced exacerbation of psoriasis–A case series and mini review - Ständer, Sascha; Zirpel, Henner; Bujoreanu, Florin; Tatu, Alin Laurentiu; Ludwig, Ralf J.; Thaçi, Diamant (Frontiers in Medicine, 2022)
Recently, COVID-19 vaccination-induced exacerbation or new-onset of psoriasis have been reported. Underlying immune pathogenesis is unclear and different mechanisms are assumed. Further, clinical- and vaccine-related features and characteristics are partly inconsistent and remain to be elucidated. To add to the understanding of COVID-19 vaccination-triggered psoriasis, we report five cases with exacerbation or new-onset of psoriasis. In our cohort, one patient experienced the new onset of psoriasis, while four had an exacerbation following COVID-19 vaccination. In most patients, exacerbation or new onset occurred after the 2nd or 3rd vaccination. The mean latency from the day of vaccination was 7.2 (1.8) days (SD). The clinical impact with a mean PASI increase following COVID-19 vaccination of 7.2 (5.6) was considered relevant. In most cases, psoriatic lesions almost cleared after applying topical steroids in addition to current treatment, while one patient with psoriatic arthritis required systemic treatment. New onset and exacerbation of psoriasis have also been noted following COVID-19 infections. Hence, the underlying inflammatory response is most likely the culprit agent triggering psoriasis. This underscores that the benefits of COVID-19 vaccination far outweigh the risks, as also in patients with psoriasis.